PENGARUH PENERAPAN STANDAR PELAPORAN AKUNTANSI SEKTOR PUBLIK DAN PENGAWASAN KUALITAS PELAPORAN KEUANGAN TERHADAP AKUNTABILITAS KINERJA PEMERINTAH PROVINSI BENGKULU (Studi Kasus : BPKD, Inspektorat, DPMD dan DPRD di Provinsi Bengkulu) - Veny Marlena; subaeti subaeti (Universitas Prof.Hazairin,SH Bengkulu, 2018)
his research uses data quality test analysis method, multiple linear regression test,hypothesis test and determination test. The calculation results obtained by theregression equation Y = 6.903+ 0.274X1 + 0.371X2, with a regression coefficient (r) of0.942 with a coefficient of determination (R Square or R2) of 0.887 this shows thatjointly the variables Implementation of Reporting Standards Public Sector Accounting(X1) and Supervision of Financial Reporting Quality (X2) on Government PerformanceAccountability (Y) is influenced by 88.7% while the remaining 11.3% is influenced byother variables not included in the study.Based on the results of partial testing shows the variable Application of Public SectorAccounting Reporting Standards (X1) and Financial Reporting Quality Supervision (X2)each variable has a significant influence on Government Performance Accountability(Y) with a tcount of 2.965 (X1) and 2.364 (X2) and t table is 1.6828 or tcount> t table soHa is accepted by Hoditolak.Based on the results of simultaneous testing shows that the variable Application ofPublic Sector Accounting Reporting Standards (X1) and Financial Reporting QualitySupervision (X2) have a simultaneous or jointly significant effect on GovernmentPerformance Accountability (Y) with fhitung> ftabel (156,768> 3.23) this means Ha isaccepted Ho is rejected.